2014
DOI: 10.1183/09031936.00046814
|View full text |Cite
|
Sign up to set email alerts
|

An official European Respiratory Society statement on physical activity in COPD

Abstract: Affiliations: For a full list of the authors' affiliations please refer to the Acknowledgements. ABSTRACT This European Respiratory Society (ERS) statement provides a comprehensive overview on physical activity in patients with chronic obstructive pulmonary disease (COPD). A multidisciplinary Task Force of experts representing the ERS Scientific Group 01.02 ''Rehabilitation and Chronic Care'' determined the overall scope of this statement through consensus. Focused literature reviews were conducted in key topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
429
3
31

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(477 citation statements)
references
References 168 publications
14
429
3
31
Order By: Relevance
“…While pulmonary rehabilitation that includes supervised exercise training is efficacious (5), several factors limit the reach of this intervention (6). Moreover, pulmonary rehabilitation and exercise training have not been consistently associated with an increase in daily levels of physical activity (2)(3)(4)7), and there are very few trials of interventions to increase physical activity among patients with COPD compared with interventions of supervised exercise training (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…While pulmonary rehabilitation that includes supervised exercise training is efficacious (5), several factors limit the reach of this intervention (6). Moreover, pulmonary rehabilitation and exercise training have not been consistently associated with an increase in daily levels of physical activity (2)(3)(4)7), and there are very few trials of interventions to increase physical activity among patients with COPD compared with interventions of supervised exercise training (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Despite concomitant increase in exercise capacity, the number of steps/day decreased in the placebo group, indicating a compensatory response to recover from the intensive exercise training sessions in daily physical activity. The observed dissociation between physical performance and daily physical activity has previously been reported in studies evaluating the effect of PR on daily physical activity22 and suggests that changing physical activity behaviour requires a more comprehensive approach than only targeting exercise capacity 23. In contrast to the placebo group, no adaptive decrease in daily steps was shown by patients receiving nutritional supplementation.…”
Section: Discussionmentioning
confidence: 54%
“…[48][49][50] Physical activity in patients with COPD is dependent on many factors, including physiological, behavioral, social, environmental, and cultural factors. 51,52 Watz and colleagues 53 have shown that daily physical activity is only weakly associated with post-bronchodilator FEV1. There is, however, a strong inverse association between daily physical activity and dynamic hyperinflation, which correlates strongly with exertional dyspnea in COPD.…”
Section: Pulmonary Research and Respiratory Medicine Issn 2377-1658mentioning
confidence: 99%
“…Pedometers are devices which estimate the number of steps taken through mechanical or digital measurements in only the vertical plane. [45][46][47] This is a limited measure of physical activity. Accelerometers detect acceleration in one, two or three directions (uni-, bi-or triaxial accelerometers).…”
Section: Pulmonary Research and Respiratory Medicine Issn 2377-1658mentioning
confidence: 99%
See 1 more Smart Citation